2018
DOI: 10.23880/mjccs-16000179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Hypertension among Nepalese Civil Servants

Abstract: Background: Hypertension is one of the major global emerging health problems in this industrial world. Prevalence of is increasing daily. Overall awareness and modifying one's lifestyle could be beneficial to the reduction of hypertension.Majority of the hypertension cases are found in the developing countries. South Asian countries such as India, Bangladesh and Nepal have a higher risk of hypertension which is rapidly increasing. Methods:Analytical cross-sectional study was conducted to determine the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Furthermore, the association between the family of diabetes mellitus and hypertension was identified using nine studies [22,23,29,32,33,48,55,56,59]; among them, four studies [22,23,48,59] showed that there is no statistically significant association between family history of diabetes mellitus and hypertension. The random effects model estimate showed that statistically significant heterogeneity between studies (I 2 = 89.9%, P-value < 0.001) and Egger's test…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, the association between the family of diabetes mellitus and hypertension was identified using nine studies [22,23,29,32,33,48,55,56,59]; among them, four studies [22,23,48,59] showed that there is no statistically significant association between family history of diabetes mellitus and hypertension. The random effects model estimate showed that statistically significant heterogeneity between studies (I 2 = 89.9%, P-value < 0.001) and Egger's test…”
Section: Plos Onementioning
confidence: 99%
“…Overall, a total number of 51,427 study participants who are older than 18 years included for this review. The minimum and maximum sample sizes were 306 and 9788 respectively [22,23]. A minimum of (7.47%) and maximum of (41.90%) prevalence of hypertension were reported from the studies conducted in the Oromia region [24,25].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Five regions and two city administrations (Addis Ababa and Dire Dawa) were represented for this review. Seven from Amhara Region [26][27][28][29][30][31][32], eight from Oromia Region [24,25,[33][34][35][36][37][38], six from South National and Nationalities of People's Region (SNNPR) [22,[39][40][41][42][43], four from Tigray Region [44][45][46][47], three from Somali Region [48][49][50], eight from Addis Ababa [51][52][53][54][55][56][57][58], two from Dire Dawa [37] and one national study in Ethiopia [23] were included. No studies reviewed from Gambela, Afar, Benishangul Gumez, and Harari Regional states of Ethiopia ( Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations